Mokken scale analysis of the Internet Gaming Disorder Scale–Short-Form and the Gaming Disorder Test - Laura Maldonado-Murciano; Halley M. Pontes; Maite Barrios; Juana Gómez-Benito; Georgina Guilera (Addictive Behaviors Reports)
In recent years, research on disordered gaming has grown substantially with researchers developing different psychometric tools for assessing it. Two of the most prominent assessment tools are the Internet Gaming Disorder Scale–Short-Form (IGDS9-SF) and the Gaming Disorder Test (GDT), which evaluate disordered gaming under the American Psychiatric Association (APA) and the World Health Organization (WHO) frameworks, respectively. The main aim of this study was to assess and compare the scalability, reliability, and validity of both scales to determine if they effectively assess disordered gaming in a normative sample, through the Mokken Scale Analysis (MSA). A sample of 605 participants (42.31 % female, meanage = 23.98 years, SD = 9.21 years) was recruited for the present study. Results showed that both the IGDS9-SF and GDT were unidimensional, with all items presenting latent monotonicity fitting in the Monotone Homogeneity Model (MHM). Item characteristic curves did not intersect and presented with adequate fit in the Double Monotonicity Model (DMM). These findings further support the psychometric adequacy of the IGDS9-SF and GDT, attesting to their suitability to assess disordered gaming.